2003
DOI: 10.1128/aac.47.1.262-267.2003
|View full text |Cite
|
Sign up to set email alerts
|

Synergistic Activity of the N-Terminal Peptide of Human Lactoferrin and Fluconazole against Candida Species

Abstract: In light of the need for new antifungal regimens, we report that at noncandidacidal concentrations, the lactoferrin-derived peptide hLF(1-11), which is highly active against fluconazole-resistant Candida albicans, acts synergistically with fluconazole against this yeast and a fluconazole-sensitive C. albicans strain as well as C. glabrata, C. krusei, C. parapsilosis, and C. tropicalis. When these yeasts were exposed to hLF(1-11) for 5 min and then incubated with fluconazole, they were killed effectively, while… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
58
0
1

Year Published

2005
2005
2023
2023

Publication Types

Select...
9
1

Relationship

1
9

Authors

Journals

citations
Cited by 89 publications
(61 citation statements)
references
References 30 publications
(129 reference statements)
2
58
0
1
Order By: Relevance
“…The peptide was highly active against fluconazole-resistant Candida albicans at non-candidacidal concentrations, acted synergistically with fluconazole against this yeast and a fluconazole-sensitive C. albicans strain, as well as against C. glabrata, C. krusei, C. parapsilosis and C. tropicalis. When these yeasts were exposed to hLf(1-11) for five minutes and then incubated with fluconazole, they were effectively killed, while no candidacidal activity was observed when they were incubated first with fluconazole and then exposed to the peptide: this shows that the candidacidal activity is initiated by the peptide, whereas fluconazole is only required during the effector phase [53].…”
Section: In Vitro Antibacterial and Anti-fungal Activity Of Lf(1-11)mentioning
confidence: 98%
“…The peptide was highly active against fluconazole-resistant Candida albicans at non-candidacidal concentrations, acted synergistically with fluconazole against this yeast and a fluconazole-sensitive C. albicans strain, as well as against C. glabrata, C. krusei, C. parapsilosis and C. tropicalis. When these yeasts were exposed to hLf(1-11) for five minutes and then incubated with fluconazole, they were effectively killed, while no candidacidal activity was observed when they were incubated first with fluconazole and then exposed to the peptide: this shows that the candidacidal activity is initiated by the peptide, whereas fluconazole is only required during the effector phase [53].…”
Section: In Vitro Antibacterial and Anti-fungal Activity Of Lf(1-11)mentioning
confidence: 98%
“…hLF1-11 has a broad antimicrobial spectrum in vitro against both bacteria and fungi (11,12,16). Furthermore, Nibbering et al demonstrated the efficacy of hLF1-11 in vivo, reducing the number of bacteria (MRSA) after systemic administration in the mouse thigh infection model (16).…”
mentioning
confidence: 99%
“…It has also been documented that several peptides have synergistic activity against C albicans when combined with fluconazole due to inhibition of production and release of intracellular ATP [28][29][30] . Because CaIPF14030 plays a critical role in regulating intracellular ATP levels, the protein encoded by CaIPF14030 may be targeted by the inhibitors of intracellular ATP.…”
Section: Discussionmentioning
confidence: 99%